108. Selective Decay of Intact HIV-1 Proviral DNA on Antiretroviral Therapy. (31st December 2020) - Gandhi, Rajesh; Cyktor, Joshua; Bosch, Ronald; Mar, Hanna; Laird, Gregory; Martin, Albine; Collier, Ann; Riddler, Sharon; Macatangay, Bernard; Rinaldo, Charles; Eron, Joseph J; Siliciano, Janet; et al.
Abstract: Background: HIV-1 proviruses persist in people on antiretroviral therapy (ART) but most are defective and do not constitute a replication-competent reservoir. The decay of infected cells carrying intact compared with defective HIV-1 proviruses has not been well-defined in people on ART. Methods: We separately quantified intact and defective proviruses (using an intact proviral DNA assay), residual plasma viremia, and markers of inflammation and activation in people on long-term ART. Longitudinal measurements were done at three timepoints: timepoint 1 was a median of 7.1 years on ART; timepoint 2 was a median of 3.7 years later; timepoint 3 was a median of 5.5 years after timepoint 1 and a median 12 years after starting ART (Figure 1). Figure 1: Study timepoints Results: Among 40 participants tested longitudinally from a median of 7.1 years to 12 years after ART initiation, intact provirus levels declined significantly over time (median half-life 7.1 years; 95% confidence interval [CI], 3.9, 18), whereas defective provirus levels did not decrease. The median half-life of total HIV-1 DNA was 41.6 years (95% CI, 13.6, 75). When we evaluated the change in proviral DNA per year, intact proviral DNA declined significantly more (p< 0.001) than defective proviral DNA (the latter did not change) (Figure 2). The proportion of all proviruses that were intact diminished over time on ART, from about 10% at the first on-ART timepoint to about 5% at the last timepoint (Figure 3). At timepoint 1, intact provirus levels on ART correlated with total HIV-1 DNA and residual plasma viremia, but there was no evidence for associations between intact provirus levels and inflammation or immune activation. Figure 2: Percent change in HIV-1 proviral DNA per year Figure 3: Total HIV-1 proviruses (grey bars) and the percentage of intact proviruses (red lines, displaying median, Q1, Q3) by timepoint. Conclusion: Cells containing intact, replication-competent proviruses are selectively lost during suppressive ART. Defining the mechanisms involved should inform strategies to accelerate HIV-1 reservoir depletion. Disclosures: Rajesh Gandhi, MD, Merck (Advisor or Review Panel member) Gregory Laird, PhD, Accelevir Diagnostics (Shareholder, Other Financial or Material Support, Employee) Albine Martin, PhD, Accelevir Diagnostics (Shareholder, Other Financial or Material Support, Employee) Bernard Macatangay, MD, Gilead (Grant/Research Support) Joseph J. Eron, MD, Gilead Sciences (Consultant, Research Grant or Support)Janssen (Consultant, Research Grant or Support)Merck (Consultant)ViiV Healthcare (Consultant, Research Grant or Support) Janet Siliciano, PhD, Gilead (Advisor or Review Panel member)US Military HIV Research Program (Advisor or Review Panel member) John Mellors, MD, Abound Bio (Shareholder)Accelevir Diagnostics (Consultant)Co-Crystal Pharmaceuticals (Shareholder)Gilead (Consultant, Grant/Research Support)Merck (Consultant)